Taxonomic revision of Schizotechium (Caryophyllaceae) in Nepal, including one new record - Kafle, Rashika; Parmar, Gaurav (Phytotaxa, 2024)
Taxonomic revision of Schizotechium (Caryophyllaceae) in Nepal was done based on the extensive study of herbarium specimens deposited in various herbaria as well as our own collections. According to this study, Nepal is home to four species of Schizotechium: S. delavayi, S. devendrae, S. monospermum and S. paniculatum. Schizotechium devendrae that was collected from several locations in Nepal is reported to be a new record for Nepal. Schizotechium delavayi and Stellaria monosperma f. scabrifolia have been found to be conspecific, but due to prior publication of S. delavayi, S. monosperma f. scabrifolia has been treated as a synonym of S. delavayi. Lectotypification has been done for Stellaria crispata, Stellaria glandulifera and Stellaria nyalamensis. Previous studies have ignored to mention a Schizotechium species as the type of the genus Schizotechium. Therefore, this study considered Schizotechium monospermum as the type species of the genus Schizotechium in order to validly publish the genus in compliance with the rules of ICN. Taxonomic treatment, habitat, distribution, photo plates, as well as keys to each species, have been provided.